Bio-inspired bicomponent fiber with multistimuli response to infrared light and humidity for smart actuators - Zheng, Qinchao (2022)
Smart actuators with multistimuli synergistic response functions can be widely used in complex environments. In this study, a torsion side-by-side sodium alginate-sodium alginate/graphene oxide (SA-SA/GO) fiber-based smart actuator with an intermittent spiral structure is reported by the side-by-side wet spinning and twisting methods. With the excellent humidity response of SA and the photothermal properties of GO, the side-by-side fiber can produce a twisting motion of 449 rpm and untwisting rotation motion of 201 rpm at full speed when stimulated by infrared (IR) light (0.5 W/cm2) or moisture (90% RH). Meanwhile, due to the unique bicomponent intermittent spiral structure of the side-by-side fiber, the SA component and the SA/GO component in the spiral structure show different response speeds to infrared light and humidity stimulus, and the actuator can complete a controllable and programmable "forward-stagnation-reverse"synergistic drive response behavior under the co-stimulation of IR light and humidity using the alternating transformation of torque force and solvation force. In addition, owing to the excellent flexibility and synergistic responsiveness of the side-by-side SA-SA/GO smart actuator, it can be prepared to form a series of programmable smart devices for the design of bionic muscles and multifunctional load devices in complex environments, which has important applications in future smart device development.